Portal vein gas is a sign of intestinal necrosis after pesticide poisoning: a case report - Huipeng Zhu; Guozhong Chen; Shiyi Liu; Keyan Hong; Huajun Wang (Journal of International Medical Research, 2024)
Portal vein gas accumulation and intestinal pneumatosis are uncommon signs indicating a high mortality risk in cases of intestinal ischemic necrosis. However, the widespread use of computed tomography has led to an increase in detection of benign lesions. We report a case of portal vein gas accumulation resulting from organophosphorus pesticide poisoning. A male patient was brought to the hospital in a comatose state with bilateral pupils that measured 1.0 mm, and he showed shortness of breath and wet rattles in the lungs. A cholinesterase concentration of 214 U/L was detected on an auxiliary examination. The patient was diagnosed with organophosphorus pesticide poisoning and underwent mechanical ventilation, hemoperfusion, and continuous renal replacement therapy according to the poisoning guidelines. On the fifth day, considerable abdominal distension was observed. An abdominal computed tomography scan revealed dilation of the small bowel and ascending colon with fluid and gas accumulation, as well as gas within the intestinal wall and hepatic veins. Although portal vein gas and intestinal pneumatosis are a sign of mortality requiring immediate surgical intervention, an increasing number of benign cases suggests potential benefits of conservative treatment approaches.